Effect of Irrigation on Evapotranspiration,Water and Energy use Efficiency of Mustard Crop - Ramakrishna, Y S; Rao, A S; Singh, R S; Joshi, N L (Annals of Arid Zone, 2016)
Performance of mustard crop grown at three levels of irrigation (100% PET, O%PET and control) was studied for two consecutive seasons in Iysimeters to ascertain its optimum water requirements. Mustard crop responded linearly upto 50% PET and thereafter the water use efficiency (WVE) decreased as a result of lower efficiency of the crop to utilise the excess available water for increasing grain production linearly. Both water and energy use efficiencies (EVE) were found to be higher during the flowering, pod formation and seed fi1ling stages of crop. Radiation profile measurements revealed that in mustard crop maintained at potential rate (100% PET), 65% of total incident radiation was absorbed by the crop during vegetative and reproductive stages as against 49% in the control crop which had 70% less leaf area compared to the crop grown at potential rate.